2018
DOI: 10.1111/jam.13681
|View full text |Cite
|
Sign up to set email alerts
|

Contact killing and antimicrobial properties of copper

Abstract: With the emergence of antibiotic resistance, the interest for antimicrobial agents has recently increased again in public health. Copper was recognized in 2008 by the United States Environmental Protection Agency (EPA) as the first metallic antimicrobial agent. This led to many investigations of the various properties of copper as an antibacterial, antifungal and antiviral agent. This review summarizes the latest findings about 'contact killing', the mechanism of action of copper nanoparticles and the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
405
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(412 citation statements)
references
References 160 publications
(285 reference statements)
6
405
0
1
Order By: Relevance
“…Limited research has so far been undertaken on the antiyeast activity of copper, however, it is widely accepted that its usability against yeast is similar to that against bacterial species. 49,50 The mechanism of 'contact killing' in S. cerevisiae and C. albicans cells has been investigated when in contact with Cu-based particles (C11000 99.9% Cu and C75200 62% Cu). 49 By modifying Cu homeostasis, it was found that the elimination of C. albicans was 4-6 times faster, when compared to Cu ATPase export and S. cerevisiae decient for Cu uptake transporters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited research has so far been undertaken on the antiyeast activity of copper, however, it is widely accepted that its usability against yeast is similar to that against bacterial species. 49,50 The mechanism of 'contact killing' in S. cerevisiae and C. albicans cells has been investigated when in contact with Cu-based particles (C11000 99.9% Cu and C75200 62% Cu). 49 By modifying Cu homeostasis, it was found that the elimination of C. albicans was 4-6 times faster, when compared to Cu ATPase export and S. cerevisiae decient for Cu uptake transporters.…”
Section: Introductionmentioning
confidence: 99%
“…This is a cluster of genes that encode the cell surface-associated glycoproteins, this could regulate the CRP1. 49,50 Non-coated CuONPs have positive surface charge at neutral pH and can electrostatically adhere to the negatively charged cell walls. The average size of CuONPs is likewise essential for their potential anti-algal activity, as smaller nanoparticles have higher portability between biological compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Copper (Cu) and its alloys are well‐known antimicrobial agents and have been used for medical purposes since ancient times . During the past decade, Cu alloys have been extensively investigated and reviewed as antimicrobial materials to reduce the spreading of bacteria or pathogen infection . It has been found that alloys with higher than 60 wt% Cu content could kill up to 99.9% bacteria, such as Escherichia coli , Staphylococcus aureus , and even fungi and virus .…”
Section: Introductionmentioning
confidence: 99%
“…10, 11 In contact with Candida albicans, copper damages the cytoplasmic membrane, producing depolarization and facilitating the entry of copper ions into the cell, inducing free radicals and increasing oxidative stress, a process called "death by contact". 12 Copper sulfate (CuSO 4 ) is a chemical compound that occurs mainly in two forms: copper sulfate I (cuprous sulfate), and copper sulfate II (pentahydrate). 11 Copper sulfate II is used in the preparation for other copper compounds in the manufacture of different fungicidal ml presentó una efectividad similar a los otros productos, en la reducción de colonias de Candida albicans.…”
Section: Introductionmentioning
confidence: 99%